Addressing Global Inequality through Modern Macroeconomic Approaches - Paulina; Adiawaty, Susi (Indonesian Scientific Publication, 2024)
This narrative review examines the theoretical and empirical developments in macroeconomic thought, focusing on the limitations of conventional models and the emergence of more inclusive and adaptive approaches. The study aims to explore how contemporary macroeconomic theory can better address global inequality, economic volatility, and institutional transformation. Using a structured literature search across Scopus, Google Scholar, and PubMed, the review employed specific keywords such as